Immunization coverage in Italy - Salmaso, S. (1987)
In Italy information on immunization coverage against pertussis, measles, and rubella is absent or incomplete. In 1985 the Istituto Superiore di Sanità (ISS) organized a series of immunization coverage surveys for these diseases in several local health units (Unità Sanitaria Locale) (USL). The surveys were conducted simultaneously in 80 USLs in 1985 with modified EPI cluster sampling techniques, using schools attended by children aged 3 to 10 years as the clusters. Information on previously performed immunizations was collected for each child sampled. The total immunization coverage and proportion of immunized children in eight birth cohorts were calculated. Low immunization coverage was reported by the USLs surveyed, and regional differences in the coverage were apparent between the north, centre, and south of Italy. In addition, a steady or decreasing trend in the use of pertussis vaccine was found, while an increasing coverage was observed for measles and rubella immunizations.